Pengaruh Teknologi Digital dan Efisiensi Operasional terhadap Profitabilitas Bank Syariah: Studi Kasus Industri Perbankan Syariah - Nurazizah, Riska (Al-Amien Prenduan for Islamic Institute, 2025)
This study aims to analyze the influence of digital technology and operational efficiency on the profitability of Islamic banks in Indonesia by using secondary data obtained from the Financial Services Authority (OJK) for the period 2005–2025. The analysis was conducted using the Ordinary Least Squares (OLS) method through EViews software to obtain an empirical description of the relationships among the research variables. The regression results indicate that digital technology, operational efficiency, and other supporting variables do not exert a significant effect on profitability, as reflected in the probability values of each variable, which exceed the 0.05 significance threshold. The regression model also shows a very low R-squared value and an insignificant F-statistic, suggesting that the model has limited ability to explain variations in profitability. Residual analysis further demonstrates that the error distribution does not fully follow a normal pattern based on the Jarque-Bera test, although the deviations remain within an acceptable descriptive range. These findings highlight that increases in digitalization and operational efficiency during the observation period have not yet translated into measurable contributions to the profitability of Islamic banks. This condition implies that the digitalization process and efficiency improvements require time, system strengthening, and managerial readiness before their impact becomes fully reflected in financial performance. Therefore, future research is recommended to incorporate additional variables, extend the observation period, and employ more comprehensive analytical approaches to obtain stronger and more representative results.